Environmental sustainability in urologic practices: a systematic review - Tozsin, A.; Aydın, Abdullatif; Silay, S.; Demet, A. E.; Knoll, Thomas; Herrmann, T.; De Bruin, M.; Dasgupta, Prokar; Rassweiler, Jens; Guven, Selcuk; Ahmed, K. (World journal of urology, 2025)
The aim of this systematic review is to assess the environmental impact of urologic procedures and equipment (P), specifically comparing emissions and waste generation between single-use and reusable devices (I and C), while also exploring strategies for emission reduction and providing relevant recommendations for sustainable practices in urology.
Gesehen am 17.06.2025